Molecular evidence for the assignment of the Cameroonian freshwater crab genus Louisea Cumberlidge, 1994, to the Afrotropical subfamily Potamonautinae Bott, 1970 (Crustacea: Potamoidea: Potamonautidae) - Ndongo, Pierre A. Mvogo; Cumberlidge, Neil; Poettinger, Theodor S.; Rintelen, Thomas Von; Tamesse, Joseph L.; Schubart, Christoph D. (Zootaxa, 2017)
The family Potamonautidae Bott, 1970, currently comprises 19 genera assigned to two subfamilies (Potamonautinae Bott, 1970, and Deckeniinae Hilgendorf, 1869) based on morphological and molecular studies (Cumberlidge 1999; Daniels et al. 2006a, 2015; Cumberlidge et al. 2008; Cumberlidge & Ng 2009). All members of this family are endemic to the Afrotropical zoogeographical region that includes most of continental Africa plus the continental islands of Madagascar, the granitic Seychelles, Socotra, and the southern Arabian Peninsula. Seven genera from sub-Saharan Africa are presently assigned to Potamonautinae (see Cumberlidge et al. 2008; Daniels et al. 2015): Erimetopus Rathbun, 1894, Liberonautes Bott, 1955, Louisea Cumberlidge, 1994, Potamonautes Bott, 1970, Potamonemus Cumberlidge & Clark, 1992, Sudanonautes Bott, 1955, and Platythelphusa A. Milne-Edwards, 1887. Twelve genera from West and East Africa, Seychelles, and Madagascar are assigned to Deckeniinae (see Cumberlidge et al. 2008; Meyer et al. 2014; Daniels et al. 2015): Deckenia Hilgendorf, 1869, Seychellum Ng, Števčić & Pretzmann, 1995, Globonautes Bott, 1959, Afrithelphusa Bott, 1969, Boreas Cumberlidge & Sternberg, 2002, Foza Reed & Cumberlidge, 2006a, Hydrothelphusa A. Milne-Edwards, 1872, Madagapotamon Bott, 1965, Malagasya Cumberlidge & Sternberg, 2002, Marojejy Cumberlidge, Boyko & Harvey, 2000, Skelosophusa Ng & Takeda, 1994, and Glabrithelphusa Meyer, Cumberlidge & Koppin, 2014.